Bluetooth Approch for Toll Tax Application - Sona, Rani (My University, 2007)
The bluetooth wireless technology was created to replace the cables used on mobile devices with radio frequency waves. The technology encompasses a simple lowcost, low-power, global radio system for integration into mobile devices, which can form a quick ad-hoc secure “piconet” and communicate among the connected devices. This technology creates many useful mobile usage models because the connections can occur while mobile devices are being carried in pockets and briefcases. Therefore, there are no line-of-sight restrictions. Bluetooth technology operates at a short-range radio frequency (RF) and is capable of transmitting voice and data. The effective range of bluetooth devices is 32 feet (10 meters). Bluetooth transfers data at the rate of 1 Mbps. The bluetooth specifications use frequency-hopping spread-spectrum technology, which entails the transmitter’s jumping from one frequency to the next at a specific hopping rate in accordance with a pseudo-random code sequence. Bluetooth wireless technology uses 79 hops per second displaced by 1 MHz, starting at 2.402 GHz and stopping at 2.480 GHz. Frequency hopping makes the transmission more secure and resistant to noise and fade. In spread spectrum technique used by bluetooth, the signal is taken apart or “spread” so that it sounds more like noise to the casual listener. Using the same spreading code as the transmitter, the receiver correlates and collapses the spread signal back down to its original form. With the signal’s power spread over a larger band of frequencies, the result is a more robust signal and it makes voice and data communications more secure. In my thesis work, I have implemented the bluetooth technology in the application of toll tax system. In the current system the difficulties are time management, payment collection and processing, long queues and manual operations. These difficulties can be removed by implementing the system using bluetooth technology. This will make the system automatic, secure and easier to operate and maintain.
Keywords: Bluetooth; Toll Tax; Encryption; Scatternet; Adhoc Networking